PHYSICAL ACTIVITY IN WOMEN AFTER BREAST CANCER TREATMENT: AN ASSESSMENT STUDY - Dariusz Nędza; Anastasiia Holoborodko; Ewa Wieczorkiewicz; Eliza Garbacz; Agnieszka Pocheć; Bartosz Lautenbach; Patrycja Stępińska; Klaudia Wojciech; Anhelina Loputs; Wiktoria Błaszczyk (International Journal of Innovative Technologies in Social Science, 2026)
Background: Breast cancer remains the most commonly diagnosed malignancy among women in Poland. Effective postoperative rehabilitation, including physical activity, plays a crucial role in restoring functional capacity, reducing complications, and improving overall quality of life. Aim: To evaluate the level of physical activity in women after surgical breast cancer treatment, considering type of surgery, presence of lymphedema, psychological factors, and changes compared with pre-treatment activity Methods: A cross-sectional survey was conducted among 58 women treated surgically for unilateral breast cancer. Data were collected using an author-designed questionnaire and the International Physical Activity Questionnaire (IPAQ). Results: Most participants were older than 55 years, retired, and had undergone radical mastectomy. Lymphedema occurred in approximately one-quarter of the women. Across all subgroups, physical activity declined after treatment, regardless of surgery type or presence of lymphedema. Most women perceived physical activity as beneficial for recovery, but a significant proportion lacked clear guidance. Conclusions: Physical activity levels decrease following breast cancer treatment, yet women recognize its value. Systematic patient education and structured rehabilitation programs should be integral to oncologic care.